Estimations of plane capacitor capacitances - Zoriy , N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
We derive an exact lower estimate for the capacity of a plane condenser in terms of logarithmic capacities of the boundary sets of its plates and study the case of an equality.